Penguatan Branding dan Pemasaran Digital UMKM melalui Pendampingan Terstruktur pada Masyarakat Terdampak Bendungan Bener - Selvi Oktafia; Dedi Runanto (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The construction of the Bener Dam as a National Strategic Project has caused major socio-economic changes in Guntur Village, Purworejo Regency, following the loss of approximately 90% of agricultural land that compelled many residents to shift to Micro, Small, and Medium Enterprises (MSMEs). This community service program aimed to strengthen MSME capacity through branding, digital marketing, and structured mentoring to support sustainable local economic resilience. The program involved 18 MSME actors and one Joint Business Group (KUBe) and was implemented through three stages: preparation, implementation, and evaluation. The implementation included MSME identification, branding and digital marketing workshops, and biweekly mentoring, while program effectiveness was assessed using pretest-posttest instruments, field observations, and business progress monitoring. The program resulted in the establishment of six new MSMEs and one KUBe, strengthened 12 existing MSMEs, improved participants’ understanding of branding and digital marketing, and expanded product promotion through social media. These outcomes demonstrate that structured mentoring combined with capacity-building activities effectively enhanced MSME competitiveness and supported the development of local flagship products. This approach provides a practical strategy for strengthening the economic resilience of communities affected by large-scale infrastructure development.